Dancing aztecs eaudiobook - Westlake, Donald E. (Mysterious Press: HighBridge Audio Classics., 2011)
From the "master of the rolling scam," here is a hilarious crime caper set in New York. A hot hustler is searching for a million-dollar Aztec sculpture that is accidentally mixed with cheap plaster copies. From Harlem to Greenwich, a motley cast chases the lost piece.